ESTIMATION OF ENTRANCE SURFACE DOSE (ESD) AS A DOSE PROFILE FOR PATIENTS UNDERGOING RADIOGRAPHY EXAMINATION BASED ON TUBE OUTPUT MEASUREMENT - Latifah, Risalatul; Rosyid, Muhammad; Yuana, Firdy; Hidayat, Achmad (Journal of Vocational Health Studies, 2020)
Background: Radiography examinations are the most widely used and indispensable tools in medical imaging. The dose received by the patient should be known to prevent the risk of radiation exposure. Patient dose in radiography examination can be best estimated in terms of entrance surface dose (ESD). ESD value can be obtained by using the recorded dose viewer installed on the device. However,  not all devices have this feature. Other methods can be conducted using thermoluminescence dosimeter (TLD) although it practically requires a high cost. Purpose: The study aims to estimate the ESD as a dose profile for patients undergoing radiography examination using tube output. Method: The patient data and exposure factors were retrospectively recorded for 263 patients. The ESD was estimated from the measurements of the X-ray tube output and recorded exposure factors.  Result: The ESD value varied from 0.002 to 0.41 mGy. In the thorax PA, thorax LAT, cervical LAT, cervical AP, skull AP, skull LAT, genu LAT and waters was found (0,23±0.05) mGy, (0,09±0,05) mGy, (0,07±0,04) mGy, (0,13±0,08) mGy, (0,03±0,01) mGy, (0,06±0,02) mGy, (0,04±0,00) mGy (0,04±0,02) mGy, respectively. These results were further used to determine the Local Diagnostic Reference Level (LDRL) value. Conclusion: The results revealed that LDRL fell below the national DRL value and international reference